Agreement of Susceptibility-Weighted Imaging (SWI) for Detecting Metastatic Brain Lesions Compared to Gadolinium-Enhanced THRIVE MRI Technique - Tritrakarn, Siri-on; Kusol, Jitlada (Asian Medical Journal and Alternative Medicine, 2021)
Introduction: To evaluate the sensitivity, agreement, and PPV of SWI for detecting metastatic brain lesions compared to Gadolinium-enhanced THRIVE MRI technique. Methods: A retrospective review of the brain MRI of metastatic brain patients on SWI and Gadoliniumenhanced THRIVE MRI technique from January, 2016 to December, 2018 which interpreted by one radiologist with ten-year experience and one third-year resident-training radiologist. The sensitivity and PPV between the SWI and THRIVE techniques were calculated. Results: A total of 17 patients with brain metastasis were enrolled. There were 11 patients (64.7%) with lung cancer, four (23.5%) with breast cancer, one (5.9%) with colon cancer, and one (5.9%) with lung and thyroid cancer. Among these 17 patients, the experienced radiologist detected 413 lesions, while the resident detected 401 lesions. According to the experienced radiologist’s results, the sensitivity of the SWI for detecting metastatic brain lesions at different sites, compared to THRIVE, ranged from 0.20 - 0.36. The PPV at different sites ranged from 0.92 - 1.00. A high PPV was suggestive of a high chance of enhancement on THRIVE of microbleed area on SWI, which indicated metastatic brain lesions. Good to excellent inter-observer agreement regarding the ICC, and substantial agreement concerning the Kappa value, were noted. Therefore, both sequences for evaluating metastatic brain lesions can be confidently used by experienced radiologists and trainee-radiologist. Conclusions: SWI has benefit for predicting hemorrhagic brain metastasis due to high PPV, especially when found coexisting with vasogenic brain edema or location at gray-white matter junction at cerebral hemisphere or cerebellar area.